Embryonic diapause due to high glucose is related to changes in glycolysis and oxidative phosphorylation, as well as abnormalities in the TCA cycle and amino acid metabolism - Hong, Jiewei; Tong, Hongxuan; Wang, Xuan; Lv, Xiaoyan; He, Lijuan; Yang, Xuezhi; Wang, Yingli; Xu, Kaixia; Liang, Qi; Feng, Qianjin; Niu, Tingli; Niu, Xin; et al. (Frontiers in Endocrinology, 2023)
The adverse effects of high glucose on embryos can be traced to the preimplantation stage. This study aimed to observe the effect of high glucose on early-stage embryos. Seven-week-old ICR female mice were superovulated, mated, and the zygotes were collected. The zygotes were randomly cultured in 5 different glucose concentrations (control, 20mM, 40mM, 60mM and 80mM glucose). The cleavage rate, blastocyst rate and total cell number of blastocyst were used to assess the embryo quality. 40mM glucose was selected to model high glucose levels in this study. 40mM glucose arrested early Running Title 2 embryonic development, and the blastocyst rate and total cell number of the blastocyst decreased significantly as glucose concentration was increased. The reduction in the total cell number of blastocysts in the high glucose group was attributed to decreased proliferation and increased cell apoptosis, which is associated with the diminished expression of GLUTs (GLUT1, GLUT2, GLUT3). Furthermore, the metabolic characterization of blastocysts was observed in the high-glucose environment. The balance of glycolysis and oxidative phosphorylation at the blastocyst stage was disrupted. And embryo development arrest due to high glucose is associated with changes in glycolysis and oxidative phosphorylation, as well as abnormalities in the TCA cycle and amino acid metabolism.